Long‐Term Outcomes of Pulmonary Vein Isolation in Patients With Brugada Syndrome and Paroxysmal Atrial Fibrillation - Antonio Bisignani; Giulio Conte; Luigi Pannone; Juan Sieira; Alvise Del Monte; Felicia Lipartiti; Gezim Bala; Vincenzo Miraglia; Cinzia Monaco; Erwin Ströker; Ingrid Overeinder; Alexandre Almorad; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background Pharmacological treatment of atrial fibrillation (AF) in the setting of Brugada syndrome (BrS) is challenging. In addition, patients with BrS with an implantable cardioverter‐defibrillator (ICD) might experience inappropriate shocks for fast AF. Long‐term outcome of pulmonary vein isolation in BrS has not been well established yet, and it is still unclear whether pulmonary vein triggers are the only pathophysiological mechanism of AF in BrS. The aim of the study is to assess the long‐term outcomes in patients with BrS undergoing pulmonary vein isolation for paroxysmal AF compared with a matched cohort of patients without BrS. Methods and Results Sixty patients with BrS undergoing pulmonary vein isolation with cryoballoon catheter ablation for paroxysmal AF were matched with 60 patients without BrS, who underwent the same procedure. After a mean follow‐up of 58.2±31.7 months, freedom from atrial tachyarrhythmias was achieved in 61.7% in the BrS group and in 78.3% in the non‐BrS group (log‐rank P=0.047). In particular, freedom from AF was 76.7% in the first group and in 83.3% in the second (P=0.27), while freedom from atrial tachycardia/atrial flutter was 85% and 95% (P=0.057). In the BrS group, 29 patients (48.3%) had an ICD and 8 (27.6%) had a previous ICD‐inappropriate shock for fast AF. In the BrS cohort, ICD‐inappropriate interventions for AF were significantly reduced after ablation (3.4% versus 27.6%; P=0.01). Conclusions Pulmonary vein isolation in patients with BrS was associated with higher rate of arrhythmic recurrence. Despite this, catheter ablation significantly reduced inappropriate ICD interventions in BrS patients and can be considered a therapeutic strategy to prevent inappropriate device therapies.